Postoperative arrhythmias in geriatric lung cancer patients undergoing thoracoscopic surgery: an exploration of prevalence and influencing factors - Xiaoyu Chen; Yan Wu; Xiaofang Zheng (Perioperative Medicine)
Abstract Background Arrhythmias are a frequent complication in the postoperative period following surgical procedures. This study aims to investigate the incidence and contributing factors of arrhythmias in elderly patients with lung cancer who have undergone thoracoscopic surgery, thereby providing scientific evidence to support clinical treatment and nursing care. Methods This retrospective cohort study included elderly patients diagnosed with lung cancer who underwent treatment at our hospital between June 1, 2022, and October 31, 2024. Patients were categorized into two groups based on the development of postoperative arrhythmias following thoracoscopic surgery: the arrhythmia group and the non-arrhythmia group. A comparative analysis of the clinical data was conducted between these two groups. Results A total of 208 patients were enrolled, with an incidence of postoperative arrhythmias of 19.71% (41/208). Logistic regression analysis identified age ≥ 70 years (OR = 2.586, 95% CI: 1.805–3.221), hypertension (OR = 2.761, 95% CI: 2.103–3.588), history of smoking (OR = 2.070, 95% CI: 1.741–2.446), TNM stage II (OR = 3.181, 95% CI: 2.842–3.690), postoperative pulmonary infection (OR = 2.122, 95% CI: 1.836–2.690), and postoperative constipation (OR = 2.495, 95% CI: 1.988–3.072) as independent risk factors for postoperative arrhythmias (all p < 0.05). Conclusion The incidence of postoperative arrhythmias in elderly patients with lung cancer following thoracoscopic surgery is relatively high. Targeted interventions addressing the identified risk factors are essential to mitigate the risk of postoperative arrhythmias.